Sola fide ou fide caritate formata : deux principes incompatibles ? - Son, Eun sil (Revue des sciences philosophiques et théologiques, 2019)
This article explores the origin of a 500-year-old misunderstanding over justifying faith. Does God justify the sinner by faith alone (sola fide), as the Lutherans say, or by faith formed by charity (fide caritate formata), as the Roman Catholics say? This is one of the most debated differences between the two traditions. A precise study of the sources and a comparison of the texts of Thomas Aquinas and Martin Luther on the interpretation of the fides caritate formata reveals that despite their different interpretations of this formula, they actually have the same understanding of justifying faith, due to their same fidelity to Scripture. It is by drawing on this common source that even today, they show the Churches a path of unity.